Forensic activity in the modern criminal process - Pilyukov, Yurii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The article examines the concept of «forensic activity», its elements, essence, purpose and procedural grounds for the appointment of examinations in criminal proceedings, the subjects of their conduct in modern criminal proceedings. For the first time at the legislative level, the term «forensic activity» is used in the Law of Ukraine «On Forensic Science». It means «activities to ensure the justice of Ukraine by an independent, qualified and objective examination». Most scholars define forensic activity as a system of actions aimed at appointing and conducting an examination in order to establish the facts of a particular criminal case, ie forensic practice. Forensic activities also include the organization of forensic institutions in general and their structural units, their scientific and methodological and information support, selection and training of forensic personnel. Thus, forensic activity covers not only the process of expert research, but also elements of expert support – scientific and methodological, legal, logistical, informational, organizational, personnel, reflects the involvement of other resources. It is believed that one of the most qualified and effective procedural forms of using special knowledge in criminal proceedings is the appointment of forensic examinations. The essence of the appointment of the examination is that the parties to the criminal proceedings and the court try to establish factual data that are essential for the investigation of the offense by using special knowledge used by the expert in the examination and can’t be obtained otherwise. The modern view of scientists on the classification of examinations, provides for their division into identification and non-identification – diagnostic, classification and situational. The organization of forensic examination consists of certain stages: preparatory, working and final. According to the latest legislative amendments to the CPC of Ukraine, the parties to criminal proceedings have the right to elect any state institution of forensic examination, or an expert that ensures the principle of procedural independence in decision-making. Therefore, the subjects of expert activity can be legal entities and individuals who organize and directly perform various types of research. Mandatory requirement for the subjects of direct research is the availability of relevant scientific knowledge in a certain field (special knowledge). Thus, during the trial, two or more opinions on the same issues may be presented as evidence at the same time, which were performed by experts from different expert institutions and agencies, both on behalf of the prosecution and the defense. In summary, it should be noted that forensic activity is a comprehensive, complete, objective and comprehensive process of research of objects, resulting in the formation and provision of scientifically sound conclusions about their properties, the possibility of the existence of certain facts and phenomena. As well as other issues that can be resolved using the expertise of experts in the investigation of criminal offenses.